THBS1 Is a Novel Serum Prognostic Factors of Acute Myeloid Leukemia - Zhu, Lidan; Li, Qiong; Wang, Xiaoguo; Liao, Jun; Zhang, Wei; Gao, Lei; Liu, Yao; Zhang, Cheng; Zhang, Xi; Rao, Jun; Kong, Peiyan (Frontiers in Oncology, 2020)
Dysregulation of cytokines and growth factors is a general feature of tumor microenvironment, unraveling the expression spectrum of cytokine and growth factor in niche is of utmost importance. Here, we evaluated cytokine profiling of bone marrow serum samples in AML patients and healthy controls. Protein expression profiling of serum from 9 AML patients and 5 healthy controls was obtained using biotinylated antibody chip. Total 507 cytokines and growth factors were analyzed. Compared with healthy people, AML patients expressed 31 signature proteins, among which, 27 were found significantly higher expressed and 4 proteins were lower. When patients were divided into favorable and poor prognosis, 12 signature proteins were significantly differentially expressed between these two groups. Furthermore, in order to identify the accuracy of cytokine expression profiles, we verified and analyzed the expression of THBS1 (Thrombospondin 1) in 116 patients and 9 healthy people. We found that THBS1 was lowly expressed in AML patients, which might be induced by promoter methylation, and patients with low THBS1 possessed shorter survivor time. Our data indicated we successfully unveil the differentially expressed proteins in AML patients by biotinylated antibody chip, among them, THBS1 may be a potential therapeutic target for AML patient’s treatment.